1992
DOI: 10.1111/j.1745-4581.1992.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

THE ANTIMICROBIAL PROPERTIES of LYSOZYME ALONE and IN COMBINATION WITH OTHER ADDITIVES IN VITRO and IN SELECTED MEAT PRODUCTS1

Abstract: Bactericidal properties of lysozyme alone and in combination wit.. other antimicrobials were studied in vitro using the microtiter system and in hotdogs and hamburger with three pathogens: Salmonella enteriditis or typhimurium, Listeria monocytogenes ATCC# 35152, and Staphylococcus aureus ATCC# 69129. Lysozyme and nisin were found to be effective against L. monocytogenes and were bactericidal in vitro at 9.27 mg/ml and 212.8 pg/ml, respectively. Twelve and one-half pg/ml nisin and 5 mg/ml lysozyme were synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover, synergy between LYS and NIS has also been demonstrated by different workers against L. monocytogenes, Brochothrix thermosphacta, Staphylococcus aureus, Carnobacterium sp. and food spoilage lactobacilli (Anderson, 1992;Chung & Hancock, 2000;Gill & Holley, 2000a, 2000bMonticello, 1990;Nattress, Yost, & Baker, 2001;Proctor & Cunningham, 1992;Takahashi et al, 2012). It was reported that the decomposition of peptidoglycan layer of bacterial cell walls by LYS, enables easy access and then subsequent binding of NIS to the sensitive cell membranes which otherwise exist buried beneath the cell surface (Dawson et al, 1996;Monticello, 1990).…”
Section: Antimicrobial Activity Of Gel Based Gel Against L Innocua In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, synergy between LYS and NIS has also been demonstrated by different workers against L. monocytogenes, Brochothrix thermosphacta, Staphylococcus aureus, Carnobacterium sp. and food spoilage lactobacilli (Anderson, 1992;Chung & Hancock, 2000;Gill & Holley, 2000a, 2000bMonticello, 1990;Nattress, Yost, & Baker, 2001;Proctor & Cunningham, 1992;Takahashi et al, 2012). It was reported that the decomposition of peptidoglycan layer of bacterial cell walls by LYS, enables easy access and then subsequent binding of NIS to the sensitive cell membranes which otherwise exist buried beneath the cell surface (Dawson et al, 1996;Monticello, 1990).…”
Section: Antimicrobial Activity Of Gel Based Gel Against L Innocua In...mentioning
confidence: 99%
“…1). The developed composite gels formed by mixing GEL with soy proteins (SP), inulin (IN) and sucrose (SUC) were incorporated with generally recognized as safe (GRAS) antimicrobials, nisin (an antimicrobial peptide) and lysozyme (an antimicrobial enzyme), that synergetic action against Listeria frequently exploited in different food systems (Gill & Holley, 2000a, 2000bMonticello, 1990;Morsy, Elsabagh, & Trinetta, 2018;Proctor & Cunningham, 1992;Sozbilen & Yemenicio� glu, 2020;Takahashi et al, 2012). The gel pH was lowered and browning of cored apple was prevented by addition of the antioxidant ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%
“…For Gram‐negative bacteria (GNB) this layer is much thinner and is covered by an outer membrane, making lysozyme much less effective as an antimicrobial agent. Several studies have investigated the activity of lysozyme against GNB 3–8. More recently, Ibrahim et al 9 reported that thermally denatured lysozyme invokes a novel antimicrobial mechanism, which is independent of its catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme is a lytic enzyme found in many natural systems including tears, plant tissues, milk, and eggs that breaks down peptidoglycan in the bacterial cell wall, resulting in cell lysis. It is active against L. monocytogenes (Hughey and Johnson, 1987), with bactericidal activity at 9.27 ng/ml in broth media (Proctor and Cunningham, 1993). A study done by Hughey et al (1989) demonstrated a marked increase in lysozyme activity against L. monocytogenes when used in conjunction with EDTA.…”
Section: Plant-and Animal-derived Compoundsmentioning
confidence: 99%
“…Spices (59) and their essential oils (22,62), sorbates (40,49), and other extracts (1,36,41) are among the most frequently studied plant-derived antimicrobials for use in/on meats. Antimicrobial compounds from animal sources have included lactoferrin (42), lysozyme (24,47), chitosan (62), and components of the lactoperoxidase system (18).…”
Section: Chapter 5 Efficacy Of Methanobactin Alone or Combined With mentioning
confidence: 99%